Flavonoids and antiulcerogenic activity from Byrsonima crassa leaves extracts - Sannomiya, M.; Fonseca, V. B.; da Silva, M. A.; Rocha, LRM; Santos, Lourdes Campaner dos [UNESP]; Hiruma-Lima, C. A.; Brito, ARMS; Vilegas, Wagner [UNESP] (Elsevier B.V., 2005)
Byrsonima crassa Niedenzu (IK) (Malpighiaceae) is used in Brazilian folk medicine for the treatment of diseases related mainly to gastric ulcers. In this study, we evaluated the potential antiulcerogenic effect of three different extracts obtained from the leaves of Byrsonima crassa namely hydromethanolic (80% MeOH), methanolic (MeOH) and chloroformic extracts (CHCl3). The oral administration (250, 500 and 1000 mg/kg) of all the extracts reduced the formation of lesions associated with HCl/ethanol administration in mice. The 80% MeOH extract significantly reduced the incidence of gastric lesions by 74, 78 and 92% at doses of 250,500 and 1000 mg/kg, respectively (P < 0.01). The MeOH extract reduced the ulceration by 93 and 99% only at the doses of 500 and 1000 mg/kg (P < 0.01). The lower gastroprotective action (69%) was observed when animals were treated with CHCl3 extract at the dose of 1000 mg/kg (P < 0.01). Phytochemical investigation of Byrsonima crassa afforded five known substances: quercetin-3-O-beta-D-galactopyranoside, quercetin-3-O-alpha-L-arabinopyranoside, the biflavonoid amentoflavone, (+)-catechin and (-)-epicatechin. The presence of these phenolic compounds may probably explain the antiulcerogenic effect of the extracts of Byrsonima crassa leaves. (C) 2004 Elsevier B.V.. All rights reserved.
Keywords: Byrsonima crassa; antiulcer activity; flavonoids; Malpighiaceae